Caesarean—Changing Values and Rising Expectations in India: Mobilizing the Drivers for Policy Concern. (June 2015) - Ravichandran, N.
Background: India is reporting an unusually increased demand for caesarean sections (CS), especially among middle class and affluent women. The present study aims to find out whether the increase in CS rates has achieved lower neonatal and maternal mortality. Method: A retrospective study using three National Family and Health Survey (NFHS) data sets—1993–1994, 1998–1999 and 2003–2004—was conducted. The study substantiated the evidence from qualitative inputs drawn from interviews from women and medical practitioners. Results: About one-eighth of all deliveries take place in the private sector; more than 30 per cent are by caesareans. Percentage of births delivered in a health facility has increased from 26.1 per cent in 1992–1993 to 40.8 per cent in 2005. Primiparous women aged below 35 years had more CSs compared to women over 35 (14 per cent in 1992–1993 to 15.5 per cent in 2005–2006 versus 7.8 per cent in 1992–1993 to 9.3 per cent in 2005–2006). The higher the woman's educational level and the household income, the more likely she is to have a CS. CS was correlated with a reduction in neonatal mortality by about 3.53 per cent in 1993–1994, 3.30 per cent in 1998–1999 and 3.07 per cent in 2005–2006. CS was also correlated with a reduction in neonatal deaths by about 3.47 per cent in 1993–1994, 2.82 per cent in 1998–1999 and 3.03 per cent in 2005–2006. Conclusion: Individuals and families along with many private hospitals hoped that emergency obstetric care initiatives would maximize return on investment, which has reached unheard-of proportions across India. It puts health systems' inefficiencies in the unenviable position of not following rationale drug use policies and ending up with the wrong kind of problem—something that does not fit well with the self-image of health care professionalism.